Long‐term changes in the gut microbiota after triple therapy, sequential therapy, bismuth quadruple therapy and concomitant therapy for Helicobacter pylori eradication in Chinese children. Issue 4 (25th April 2021) - Zhou, Ying; Ye, Ziqing; Wang, Yuhuan; Huang, Zhiheng; Zheng, Cuifang; Shi, Jieru; Tang, Wenjuan; Zhang, Ping; Wang, Shengnan; Huang, Ying
Abstract: Background: We previously reported that the administration of 14‐day standard triple therapy (TT), sequential therapy (ST), bismuth‐based quadruple therapy (BT), and concomitant therapy (CT) as the first‐line therapy for Helicobacter pylori infection in Chinese children achieved eradication rates of 74.1%, 69.5%, 89.8%, and 84.6%, respectively. In this follow‐up study, we further evaluated the short‐ and long‐term effects of the four regimens on the gut microbiota in these children. Methods: We prospectively recruited treatment‐naïve children with H. pylori infection. Fecal samples were collected at week 0, 2, 6, and 52, and alterations in the gut microbiota were analyzed by 16S rRNA gene sequencing. Results: Sixty‐three patients participated in this study (16 with TT, 15 with ST, 16 with BT and 16 with CT). At week 2, the alpha diversity (Shannon and Chao 1 index) was significantly reduced in the TT ( p = 0.008, p < 0.001), ST ( p < 0.001, p < 0.001), BT ( p < 0.001, p < 0.001) and CT groups ( p < 0.001, p < 0.001). Some changes persisted in the ST, BT, and CT groups at week 6, and all were restored (expect p = 0.02 with Chao 1 index in the CT group) at week 52. The beta diversity was significantly changed in the BT ( p = 0.001) and CT groups ( p = 0.001) 2 weeks post‐eradication and restored 1 year after therapy. Immediately after therapy, the relative abundance of Proteobacteria was strikingly increased in the ST ( p = 0.005), BT ( p < 0.001) and CT groups ( p < 0.001), and the genus‐level analysis showed that the abundances of 23.1%, 43.3%, 78.6%, and 78% of the bacterial genera in the TT, ST, BT, and CT groups were significantly changed. All these changes returned to almost the pre‐eradication level 1 year post‐eradication. Conclusion: Eradication of H . pylori infection can lead to transient dysbiosis of gut microbiota, and these changes almost recovered 1 year post‐eradication, which indicates the long‐term safety of H . pylori therapy.